Transforming Dementia Care Through Pragmatic Clinical Trials Embedded in Learning Healthcare Systems. (26th June 2020) - Tuzzio, Leah; Hanson, Leah R.; Reuben, David B.; Baier, Rosa R.; Gurwitz, Jerry H.; Bayliss, Elizabeth A.; Williamson, Jeff; Fraser, James R.; Sherman, Samantha J.; Larson, Eric B.
Abstract : The current evidence base for testing nonpharmacological interventions for people living with dementia (PLWD) and their caregivers is limited, especially within care settings such as ambulatory care, assisted living communities, nursing homes, hospitals, and hospices. There has been even less attention to translation of effective interventions for PLWD into delivery of care. Thus, there is an urgent need for researchers to partner with these care settings, especially those that follow a learning healthcare systems (LHSs) model, and vice versa to conduct embedded pragmatic clinical trials (ePCTs). These trials are conducted within sites that offer routine care and are designed to answer important, relevant clinical questions and leverage existing electronic health and administrative data. ePCTs set in LHSs create a unique opportunity for researchers, healthcare providers, and PLWD and their families to work and learn together as potentially effective interventions are studied and stress tested in real‐world situations. Healthcare settings that embrace research or quality improvement as part of a culture of continuous learning are ideal settings for ePCTs. In this article, we summarize what we have learned from the National Institutes of Health's Health Care Systems Research Collaboratory–funded ePCTs, discuss challenges of ePCTs within settings that serve PLWD, and describe the work of the Health Care Systems Core within the National Institute on Aging's IMbedded Alzheimer's Disease and Related Dementias Clinical Trials Collaboratory that will occur over the next 5 years. J Am Geriatr Soc 68:S43–S48, 2020 .